Polymorphisms in the Wilms Tumor Gene Are Associated With Interindividual Variations in Rubella Virus–Specific Cellular Immunity After Measles-Mumps-Rubella II Vaccination. (14th December 2017) - Voigt, Emily A; Haralambieva, Iana H; Larrabee, Beth L; Kennedy, Richard B; Ovsyannikova, Inna G; Schaid, Daniel J; Poland, Gregory A
Abstract : We conducted a genome-wide association study on 1843 subjects to identify genetic polymorphisms associated with cellular immunity after rubella vaccination. We identified single-nucleotide polymorphisms in the Wilms tumor gene WT1 that was significantly associated with interindividual differences in subject rubella-specific interleukin 6 secretion. Abstract: Rubella vaccination induces widely variable immune responses in vaccine recipients. While rubella vaccination is effective at inducing immunity to rubella infection in most subjects, up to 5% of individuals do not achieve or maintain long-term protective immunity. To expand upon our previous work identifying genetic polymorphisms that are associated with these interindividual differences in humoral immunity to rubella virus, we performed a genome-wide association study in a large cohort of 1843 subjects to discover single-nucleotide polymorphisms (SNPs) associated with rubella virus–specific cellular immune responses. We identified SNPs in the Wilms tumor protein gene ( WT1 ) that were significantly associated ( P < 5 × 10 –8 ) with interindividual variations in rubella-specific interleukin 6 secretion from subjects' peripheral blood mononuclear cells postvaccination. No SNPs were found to be significantly associated with variations in rubella-specific interferon-γ secretion. Our findings demonstrate that genetic polymorphisms in the WT1 gene in subjects of European ancestry are associated with interindividual differences in rubella virus–specific cellular immunity after measles-mumps-rubella II vaccination.